Cognitive Control Processes and Functional Cerebral Asymmetries: Association with Variation in the Handedness-Associated Gene LRRTM1 - Beste, Christian; Arning, Larissa; Gerding, Wanda M; Epplen, Jörg T; Mertins, Alexandra; Röder, Melanie C; Bless, Josef J; Hugdahl, Kenneth; Westerhausen, René; Güntürkün, Onur; Ocklenburg, Sebastian (Molecular neurobiology, 2018)
Cognitive control processes play an essential role not only in controlling actions but also in guiding attentional selection processes. Interestingly, these processes are strongly affected by organizational principles of the cerebral cortex and related functional asymmetries, but the neurobiological foundations are elusive. We ask whether neurobiological mechanisms that affect functional cerebral asymmetries will also modulate effects of top-down control processes on functional cerebral asymmetries. To this end, we examined potential effects of the imprinted gene leucine-rich repeat transmembrane neuronal 1 (LRRTM1) on attentional biasing processes in a forced attention dichotic listening task in 983 healthy adult participants of Caucasian descent using the "iDichotic smartphone app." The results show that functional cerebral asymmetries in the language domain are associated with the rs6733871 LRRTM1 polymorphism when cognitive control and top-down attentional mechanisms modulate processes in bottom-up attentional selection processes that are dependent on functional cerebral asymmetries. There is no evidence for an effect of LRRTM1 on functional cerebral asymmetries in the language domain unrelated to cognitive control processes. The results suggest that cognitive control processes are an important factor to consider when being interested in the molecular genetic basis of functional cerebral architecture.
Keywords: akustická stimulace; dospělí; LRRTM1; funkční lateralita; průzkumy a dotazníky; Female; Smartphone; pozornost; Acoustic Stimulation; Adult; Functional Laterality; mladý dospělý; ženské pohlaví; Surveys and Questionnaires; Adolescent; Genetics; Attention; Cerebral asymmetries; Cognitive control; lidé; membránové proteiny; jazyk (prostředek komunikace); proteiny nervové tkáně; kognice; Nerve Tissue Proteins; Male; Young Adult; Cognition; Language; Membrane Proteins; mozková kůra; Cerebral Cortex; mužské pohlaví; mladiství; Dichotic listening; Humans